Evaluación técnico-financiera de las operaciones de perforación para la disminución de los tiempos no productivos durante los viajes en los pozos seleccionados del Campo Castilla (2016)
This project begins with the geological description of the Castile Field, its location, access routes and geological characteristics of the oil present in it. It is also constituted by the geological and structural framework, ending with the production history of the field from the year 2000. With an approach of the different parameters that are part of a drilling operation and of the different types of wells that can be had in a field and emphasizing the details that characterize the wells that are evaluated in the present project taking into account The non-productive times accumulated for the year 2015, a selection of representative wells is made, thanks to its characteristics, a detailed evaluation of their non-productive times, their causes, solutions and future decline.